Evaluating the effects of environmental disturbances and pesticide mixtures on N-cycle related soil microbial endpoints - Drocco, Camilla; Coors, Anja; Devers, Marion; Martin-Laurent, Fabrice; Rouard, Nadine; Spor, Ayme (Peer Community Journal, 2025)

(untitled)
Pesticides are widely used in conventional agriculture, either applied separately or incombination during the culture cycle. Due to their occurrence and persistence in soils, pesticideresidues may have an impact on soil microbial communities and on supported ecosystemservices. In this regard, the EFSA (European Food Safety Authority) recently published ascientific opinion inciting to change pesticide risk assessment to better protect soil microbe-mediated processes. Climate change is another major concern for all living organisms includingsoil microbial community stability. Extreme climatic events, such as heat waves or heavyrainfalls, are becoming more and more frequent and their impact on soil microbial diversity andfunctions have already been demonstrated.The objectives of this study were to evaluate the effects of temperature and humiditydisturbances and pesticide active ingredients exposure on soil microbial community structureand functions. To this end, 250 soil microcosms were exposed to either a heat disturbance, ahigh humidity to mimic heavy rain, or no environmental disturbance. After three days ofrecovery, soil microcosms were treated with different active ingredients: clopyralid (herbicide),cypermethrin (insecticide) and pyraclostrobin (fungicide). The treatments were applied aloneor in combination at 1x or 10x of the agronomical dose. We then evaluated the effects of thedisturbances and the active ingredients on various microbial endpoints related to the diversityand the structure of soil microbial communities, and with a specific focus on microbial guildsinvolved in nitrification.Overall, we demonstrated that the impact of environmental disturbances applied to soilmicrocosms, especially heat, on microbial endpoints was stronger than that of the activeingredients applied alone or in combinations. Compounded effects of environmentaldisturbances and active ingredients were detected, but sparsely and were of small scale for thechosen pesticides and applied doses.